Perancangan Aplikasi Pengenalan Kebudayaan dan Pariwisata Kabupaten Cianjur Berbasis Android - Irawan, Barda; Rosyani, Perani (TIN: Terapan Informatika Nusantara, 2022)
Mobile technology is now developing very rapidly so it is very suitable to be used as a medium to introduce culture and tourism in Cianjur Regency, especially Android-based mobile technology. Android is an operating system for Linux-based mobile software that includes an operating system, middleware and applications. Android provides an open platform for developers to create an application. Culture and tourism are closely related to society. The development of culture and tourism will also affect people's lives later. Currently, efforts to introduce or promote culture in Indonesia are still very limited, especially in the Cianjur Regency area. With the approach of using an Android-based mobile application, it is hoped that the community, especially the younger generation, can more easily access this application and can find out in detail the culture and tourism of Cianjur Regency itself. The system development methodology used is the waterfall model. With the presentation of information and the appearance of the application of the introduction of culture and tourism in Cianjur Regency, the community, especially the younger generation, will be more familiar with their culture and tourism, which is very important so that cultural values ​​are not lost in time.